Backbone NMR assignments of HypF-N under conditions generating toxic and non-toxic oligomers - Patel, Jayneil R. (Biomol NMR Assign, 2018)
The HypF protein is involved in the maturation and regulation of hydrogenases. The N-terminal domain of HypF (HypF-N) has served as a key model system to study the pathways of protein amyloid formation and the nature of the toxicity of pre-fibrilar protein oligomers. This domain can aggregate into two forms of oligomers having significantly different toxic effects when added to neuronal cultures. Here, NMR assignments of HypF-N backbone resonances are presented in its native state and under the conditions favouring the formation of toxic and non-toxic oligomers. The analyses of chemical shifts provide insights into the protein conformational state and the possible pathways leading to the formation of different types of oligomers.